2009
DOI: 10.1002/art.24554
|View full text |Cite
|
Sign up to set email alerts
|

Intervention of an inflammation amplifier, triggering receptor expressed on myeloid cells 1, for treatment of autoimmune arthritis

Abstract: Conclusion. TREM-1 ligation contributes to the pathology of autoimmune arthritis. The results of this study implied that blockade of TREM-1 could be a new approach to rheumatic diseases that is safer than the presently available immunosuppressive treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 44 publications
2
49
0
2
Order By: Relevance
“…64 Finally, a recent study also found a TREM-1 upregulation in peripheral blood cells from patients suffering from spondylarthropathy. 65 Thus, while TREM-1 role in acute inflammation, especially during sepsis, is today better understood, its function during chronic rheumatic diseases only begins to be elicited.…”
Section: Effects Of the Trem-1 Pathway Modulation During Inflammatorymentioning
confidence: 90%
“…64 Finally, a recent study also found a TREM-1 upregulation in peripheral blood cells from patients suffering from spondylarthropathy. 65 Thus, while TREM-1 role in acute inflammation, especially during sepsis, is today better understood, its function during chronic rheumatic diseases only begins to be elicited.…”
Section: Effects Of the Trem-1 Pathway Modulation During Inflammatorymentioning
confidence: 90%
“…Quantitative real-time PCRs for IL-6, TNF-a, IRAK1, and GAPDH were carried out as previously described (21,22). A p16 INK4a gene-specific primer set was purchased from Qiagen (Tokyo, Japan).…”
Section: Quantification Of Cytokine and Irak1 Expressionmentioning
confidence: 99%
“…1A) [13, 15, 2324]. While the natural TREM-1 ligand is not yet known, based on a new model of immune signaling, the signaling chain homooligomerization (SCHOOL) model [25], we have developed a novel, ligand-independent approach to TREM-1 inhibition (Fig.…”
Section: Introductionmentioning
confidence: 99%